Desenvolvimento de sistemas visando o tratamento de lesões cutâneas à base de fibras de PLA/PEG e própolis vermelha produzidas por solution blow spinning - Dias, Rebeca Tibau Aguiar (2019)
Wound healing is a complex physiological process whose goal is to restore the tissue after a trauma. This area is of great interest in the development of wound dressings through the association of biomaterials with natural active principles. In this work we characterized the red propolis ethanolic extract (RP), optimized the development of fiber mats made of poly(ᴅ-lactic acid) (PLA) and produced fibers of PLA and poly(ethylene glycol) (PEG) blends in different proportions (w/w) (PLA:PEG 100:0, 90:10, 80:20 and 70:30) containing 16% w/w of RP by the solution blow spinning (SBS) system with the purpose of healing cutaneous wound. RP was evaluated through its antioxidant and antimicrobial activities and the fiber properties were characterized by SEM; physical-chemical by TGA, FTIR and XRD; adsorption, encapsulation efficiency and RP’s flavonoids release by UVvis; microbiological by Staphylococcus aureus growth kinetics; and immunological by cytotoxicity with different RP concentrations, oxidative stress through reactive oxygen species (ROS) and cytokine modulation. PLA solutions were dissolved in dimethylcarbonate (DMC) in 8, 10 and 12% w/v concentrations and spun at 80, 100 e 120 L.min-1. Results show that the polymeric concentration was the main factor to increase the fiber diameters statistically (p<0,05). From optimized condition, PLA fibers with PEG showed smooth surfaces and few beads. The mats with RP showed sustained release in time function, but 70PLA.20RP. In relation to S. aureus growth, it was observed that this microorganism was inhibited in different times to each PLA/PEG proportion. In the immunologic evaluation, fibers with less than 1% w/w of RP showed cellular viability greater than 75% in contact with peripheral blood mononuclear cell, low reactive oxygen species (ROS) formation and IL-4 and IL-10 modulation in PHA presence. PLA/PEG with RP fibers have the potential to assist the healing process to their microbial inhibition associated to cellular viability and cytokine modulation with different actuation modes in function of its wettability and controlled release of RP